(untitled) (Anwer Khan Modern Medical College Journal, 2015)
Kawasaki disease is an acute necrotizing vasculitis of the medium and small-sized vessels and has life-threatening predisposition to involve coronary arteries. The diagnosis of KD still relies on the clinical criteria. We are reporting a case of classic presentation of Kawasaki disease. Anwer Khan Modern Medical College Journal Vol. 6, No. 1: January 2015, Pages 42-45